Prognostic implications of coronary artery disease and stress tests in patients with elevated left ventricular filling pressure and preserved ejection fraction - Seo, Jeong Hun; Hong, David; Youn, Taeho; Lee, Seung Hun; Choi, Ki Hong; Kim, Darae; Park, Taek Kyu; Lee, Joo Myung; Song, Young Bin; Choi, Jin-Oh; Hahn, Joo-Yong; Choi, Seung-Hyuk; et al. (Frontiers in Cardiovascular Medicine, 2022)
Background: The prognostic role of myocardial ischemia in patients with heart failure with preserved ejection fraction (HFpEF) has not been fully elucidated. Therefore, we investigated the change in echocardiographic parameters and clinical outcomes based on the presence of epicardial coronary artery disease (CAD) and positive stress tests in HFpEF patients. Methods: Symptomatic patients with left ventricular end diastolic pressure ≥15 mmHg who underwent coronary angiography were analyzed between January 2000 and August 2019 after exclusion of patients with acute coronary syndrome. Results: A total of 555 HFpEF patients were invasively confirmed, 285 (51%) had angiographically-proven CAD. HFpEF patients with CAD displayed greater deterioration in left ventricular ejection fraction (p = 0.002) over time but this was not observed in those without CAD (p = 0.99) on follow-up echocardiography; however, the mitral annulus early diastolic velocity (e’) was significantly decreased in both groups (p < 0.001 and p = 0.003, respectively). Among 274 patients that received stress tests, those with positive stress tests showed a decline in e’ (p < 0.001), but this was not found in subjects with negative stress tests (p = 0.44). There was no significant difference in all-cause mortality between patients with CAD and without CAD (p = 0.26) with a median follow-up of 10.6 years. Conclusion: In HFpEF patients, CAD was associated with greater deterioration in the left ventricular systolic function but not with mortality during the follow-up. In addition, myocardial ischemia with a positive stress test may contribute to greater deterioration of diastolic dysfunction.